2020
DOI: 10.1177/2096531119890142
|View full text |Cite
|
Sign up to set email alerts
|

Shadow Education in Europe: Growing Prevalence, Underlying Forces, and Policy Implications

Abstract: Purpose: Private supplementary tutoring, widely known as shadow education, has long been visible in East Asia, and now has spread to other parts of the world including Europe. This article maps the phenomenon, showing variations within Europe and analyzing its growth, underlying forces, and policy implications. Design/Approach/Methods: The article assembles a regional picture from available national sources. It focuses on the 28 members of the European Union. Findings: Within Europe, four subregions may be ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(76 citation statements)
references
References 48 publications
4
61
0
11
Order By: Relevance
“…been multiple controversies and distortions, which are characterized by intense inequality between public and private schools, spectacular intrusion of shadow education practices, and frequent -yet, unsuccessfulreforms of the educational laws and legislation (Bray, 2020), thus contributing to increased inconsistency and confusion. Therefore, the combination of the adjusted translation with the educational situation in Greece, might explain the questionable functioning of the educational U-MICS in its current form.…”
Section: Discussionmentioning
confidence: 99%
“…been multiple controversies and distortions, which are characterized by intense inequality between public and private schools, spectacular intrusion of shadow education practices, and frequent -yet, unsuccessfulreforms of the educational laws and legislation (Bray, 2020), thus contributing to increased inconsistency and confusion. Therefore, the combination of the adjusted translation with the educational situation in Greece, might explain the questionable functioning of the educational U-MICS in its current form.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, research on ST shows that teachers figure more often as tutors in some countries with long histories of private ST. Students often figure as tutors in many parts of the world as well, for example, in Bangladesh (Imtiaz 2018) and the Czech Republic (Šťastný 2017). In an overview of for-profit ST in the European Union Bray (2011Bray ( , 2020 showed that private tutors in some Western European countries such as Belgium, Denmark, and Sweden (see Hallsén and Karlsson 2019 for more about tutors in Sweden) are often university students without any professional tutor or teacher training. According to Bray, big ST companies, working in national or international arenas in Western Europe, mainly employ untrained young tutors working part time.…”
Section: Research On Private Tutorsmentioning
confidence: 99%
“…In some parts of the world, the tutor is a taken-for-granted actor in the education of most children, while in others, they are a resource available only to the wealthy (Bray 2006). Private ST is often conceptualised as a form of 'shadow education' (Bray 2020), shadowing, or working in the shadows of, formal education. According to Mori and Baker (2010, 39), however, there is so much evidence of private ST coming out of the shadows and spreading worldwide that its practices 'appear to be on the verge of becoming a standard feature of education in most nations'.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time there is an ever-increasing body of literature on the privatization of education and the conceptualization of public and private spaces of learning, often with blurred frontiers . Bibliographic research demonstrates that scholars have generated significant research literature not only in Asia, which has traditionally been a major area for tutoring, but also in Europe (Bray, 2020) . This positive tendency has led scholars to develop comprehensive thematic literature in the form of special issues in scholarly journals, such as the Journal of Education Research Online (Guill & Spinath, 2014), the Asia Pacific Journal of Education (Manzon & Areepattamannil, 2014), the East China Normal University Review of Education (Zhang & Bray, 2019), or the European Journal of Education (Győri, 2020).…”
Section: Editorial Throwing Light On Shadow Educationmentioning
confidence: 99%